Pengembangan Modul Fisika Berbasis Saintifik Berbantuan QR Code Pada Materi Termodinamika Kelas XI - Nuku Hiva Hariyanto; Dasmo Dasmo; Asep Setiadi (UNIVERSITAS INDRAPRASTA PGRI, 2022)
This study aims to determine the module development process, the feasibility of the module and the response of students to the development of scientific-based thermodynamics learning modules with the help of a qr code. In this case, the qr code serves as a link to access various learning videos, as well as questions in the learning module. The method used in this research is research and development. The model used is a 4-D model. The development of the 4-D model consists of 4 stages, namely Define, Design, Development, and Disseminate. The scientific-based thermodynamics learning module assisted by qr code was declared feasible to use with validation from material experts 90.97% with very reasonable interpretation, media experts 77.50% proper interpretation and linguistic experts 92.50% very proper interpretation. And the response test was 30 students with a score of 87.20% in the very good category.